Features, Restrictions, and Policy Recommendations in the Service Sector of the People's Republic of China - Wang Wei (Asian Development Bank (ADB), 2013)
The development of the service sector in the People's Republic of China has not kept pace with the country's overall economic development. The share of employment in services is still lagging behind that of output and is also below the international norm. Moving from traditional services to modern business services has been the focus in recent decades, but the current structure is still dominated by low-end, traditional industries. In addition, due to the ongoing government strategy to make pilot reforms industry by industry, state-owned service providers still have a large market share, especially in some important service industries, and there are great disparities in development among non- state-owned service providers across various industries. Complicated institutional restrictions and a lack of effective institutional support and regulatory enforcement require in-depth reforms if the sector is to realize its potential. Strategic measures and policy options for promoting the sector in the next 10 years are suggested.
hdl:11540/2090
Keywords: O14; O40; O47; 330; services; People's Republic of China; growth; productivity